TURMÍSLÍQ MOTIVLERDEGI TIPOLOGIZM (qaraqalpaq hám qazaq xalıq ańızları mısalında) - Allambergenova, I. (ILIM hám JÁMIYET, 2025)
This article discusses the issue of typology in Karakalpak and Kazakh folklore. Karakalpak and Kazakh tales are analyzed. The issue of typology of tales in oral folk art has not yet been studied, especially the typology of Karakalpak and Kazakh tales, typological plots, typological images have not been taken into account in the research. Comparative studies of Karakalpak and Kazakh folk tales are still a relevant topic. Sultan Saray, Aksha Kol, Guldursun, Ketenler, Kozı Korpesh and Bayan Suluv and other tales are analyzed in this article.